2018
DOI: 10.1007/s11060-018-2958-6
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic models for patients with brain metastases after stereotactic radiosurgery with or without whole brain radiotherapy: a validation study

Abstract: All models under-predicted MS and only the BSKN and Lung-molGPA model stratified patients into three risk groups with statistically significant actual MS. The prognostic groupings of the adenocarcinoma Lung-molGPA group was the best predictor of MS, and showed that we are making improvements in our prognostic ability by utilizing molecular information that is much more widely available in the current treatment era.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 25 publications
0
6
0
1
Order By: Relevance
“…In addition, we found that the PIs in our study were not uniformly recommended in different studies, and there was a large discrepancy between the expected and actual survival[18, [40][41][42]. This nding supports the need for a better prognostic tool or index.…”
Section: Discussionmentioning
confidence: 59%
“…In addition, we found that the PIs in our study were not uniformly recommended in different studies, and there was a large discrepancy between the expected and actual survival[18, [40][41][42]. This nding supports the need for a better prognostic tool or index.…”
Section: Discussionmentioning
confidence: 59%
“…In the only study to date that validated the molGPA score, 70% of patients received WBRT and concurrent systemic therapy was likewise not recorded [18]. Other available scores have been shown to underestimate OS as these were all developed before widespread implementation of TT/IT [19]. Two studies have aimed to validate prognostic scores in TT/IT-treated patient cohorts that received concomitant SRT to date, albeit omitting the most widely used molGPA score [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Ideally, patients with limited prognosis would not be exposed to the unnecessary burden of intense treatment, whereas those with better prognosis would receive the therapeutic measures required to prevent neurologic death [11,12]. Several tools (prognostic scores and nomograms with survival and other endpoints) have been developed to support decision-making [13][14][15][16][17]. Initially, they were heavily based on performance status and extracranial disease extent or control, and not stratified by primary cancer type.…”
Section: Introductionmentioning
confidence: 99%